Introduction. Issue 4 (1st October 2020) - Finder, Gabriel N.; Skorczewski, Dawn; Stone, Dan
ABSTRACT: This special issue of the Journal of Holocaust Research is dedicated to Professor Lawrence Langer on the occasion of his ninetieth birthday. In the introduction we trace the enormous impact of Prof. Langer's work on Holocaust Studies, noting how his ideas have inspired scholars working in several disciplines. After Prof. Langer's autobiographical reflections on working as a scholar of the Holocaust for many decades, the following articles address issues relating to Holocaust literature, the collection and interpretation of Holocaust testimonies, Holocaust film and photography. They discuss examples ranging from Romania to France, American culture and Polish Jewry, and all illustrate how Prof. Langer's ideas continue to enrich and enliven research and debates in Holocaust Studies.